Measuring Economic Growth with a Fully Identified Three-Signal Model - Civelli, Andrea; Gaduh, Arya; Yousuf, Ahmed Sadek (The Review of Economics and Statistics, 2024)
We augment Henderson et al. (2012)'s two-signal model of true GDP growth with a third signal to overcome its underidentification problem. The additional moment conditions from the third signal help fully identify all model parameters without ad-hoc calibrations of the GDP's signal-to-noise ratio. We characterize the necessary properties of the third signal. Using the model, we recover the optimal weight of official GDP in the composite true GDP growth estimates, which varies with the quality of the national statistics. The model improves on existing methodologies that use signals to measure true income.